The levels and correlates of paratransit use in Egypt and Lebanon before and during the outspread of COVID-19 - Dief-Allah, Dina Maarouf Ahmed; Dawoud, Sofia Ayad; Khalifa, Basma; Masoumi, Houshmand (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Although studies address informal public transportation or paratransit, investigating the behavior and preferences regarding this mode in the Middle East and North Africa have not been proportional to its importance. Furthermore, with the outbreak of Covid-19, the relationship between paratransit use and different behaviors and preferences had to be investigated. Thus, this study aims to find the determinants of paratransit use for commute and non-commute purposes during and after the pandemic. The data of this study (N=3285) is based on a survey conducted in Lebanon and Egypt from 2021 till 2023. The study aimed to answer three questions: how the correlates of choosing paratransit for non-commute travels in Egypt and Lebanon changed during the COVID-19 pandemic compared to before it, how the correlates of choosing paratransit for commute travel in Egypt and Lebanon changed during the pandemic compared to before, and was paratransit use in the four cities of Cairo, Alexandria, Beirut, and Jounieh different before and during COVID-19. The results of Binary Logistic modeling and Chi-square test of independence indicates a significant difference in the level of using paratransit throughout the four cities. Moving forward, these results can regulate and guide policymaking of paratransit use in the MENA region.